'Homeliness meant having the fucking vacuum cleaner out': the gendered labour of maintaining conference communities. Issue 1 (2nd January 2020) - Burford, James; Bosanquet, Agnes; Smith, Jan
ABSTRACT: This article extends examinations of the gendered nature of care and service in academia, with a particular focus on the labour of maintaining conference communities. Utilising empirical data from a cultural history of the International Academic Identities Conference, we draw on interviews with 32 conference organisers, keynote speakers and participants to explore the gendered dynamics of reproducing conference communities. While some participants experienced exclusions, most participants described a conference that felt caring, welcoming and like 'home'. Following this discussion, we interrogate the idea of the conference as 'home', asking questions about the gendered division of 'academic housekeeping' practices that underpin such home-making. Engaging with feminist theorising of emotional labour, we argue that academic women undertook significant, and often hidden, care and service labour to maintain a homely conference community.